Sistemática de Bethylinae (Hymenoptera, Bethylidae) - Ramos, Magno Suprani (2017)
The genera of Bethylinae are clearly different one from another. The most of Bethylinae species are known only by the female sex. Their taxonomic boundaries can be considered well established, except for Goniozus Förster. Undoubtedly it is the genus with the highest degree of taxonomic confusion regarding its boundaries. The important characters delimiting Goniozus are also shared by several Bethylinae genera, making classification uncertain and hampering understanding of character evolution and variation between taxa. This subfamily currently comprises approximately 540 species described worldwide classified in eight extant genera with low sexual dimorphism. The phylogeny of Bethylinae lineages has received attention by Sorg in 1988, Polaszek & Krombein in 1994, Terayama in 1995 and De Ploëg & Nel in 2004. In all previous analyses performed there is a basal polytomy among Eupsenella, Lytopsenella and the remaining Bethylinae genera. Here we aimed 1) to review the fossil species of Bethylinae, providing descriptions and illustrations when necessary. In addition, o provide a new key to the fossil species of Bethylinae; 2) to recognize, define and describe Afrobethylus as a new Bethylinae genus, its new species. In addition, to define their diagnostic characteristics, as well as provide a key to species of Afrotropical region based on females; 3) to propose a phylogenetic hypothesis based on morphological data of the genera of Bethylinae drawing especial attention to Eupsenella and Lytopsenella relationships with the other genera of this subfamily; 4) to investigate and discuss the main diagnostic characters of Bethylinae genera. Examined material was provided by several institutions. The descriptions, character list, character matrices for cladistic analysis and key, when necessary, were elaborated with o software DELTA. The searches for the most parsimonious trees were carried out under the software TNT. Here, based on our results, we considered that the fossil genus Protobethylus De Ploëg & Nel, 2004 is a junior synonymous of Eupsenella Westwood, 1874. In addition, based on our rescue and compilation of whole the existing information in Bethylinae the fossil family Fushunochrysidae proposed by Hong in 2002 was synonymized with Bethylidae Haliday, 1839. The single genus of this family is Fushunochrysites Hong, 2002 and its single species F. eocenicus Hong, 2002 was established as its type-species. Here, we propose that the best placement of this monotypic genus in Bethylidae is into Bethylinae. Fushunochrysites displays on its forewing several characters that are also present in all members of Eupsenella. Moreover, Sinibethylus Hong, 2002 from Chinese Xilutian coal mine is here also synonymized with Eupsenella. Finally, the last synonymy of genus proposed here is related to Messoria that was described originally by Meunier in 1916. We here propose 10 Messoria as a new junior synonym of Goniozus and transfer its single Messoria copalina Meunier, 1916 to Goniozus. In addition, based on an unusual combination of characters never seen before to Bethylinae we describe Afrobethylus as a new Bethylinae genus. This Bethylinae genus is the unique excluviley Afrotropical. In the phylogenetic context, the resulting matrices contain a total of 61 species of Bethylinae terminals as ingroup, with a total of 43 characters were coded for males and a total of 87 species, 44 characters were coded for females. The resampling analyses based on both males and females returned support for a sister-group relationship among all extant Bethylinae genera. All genera were retrieved as lineages in both analyses, except Goniozus that was retrieved as paraphyletic in all analyses performed. Our most remarkable result obtained was the resolution of the existing basal polytomy in Bethylinae between Lytopsenella and Eupsenella with the other extant Bethylinae genera. In all analyses performed, these genera were retrieved by the first time as sister-group each other and separated from the other genera in all analyses performed. Based on our results, we discuss the main diagnostic characters of Bethylinae genera mainly present in the antenna, forewing, and finally by the first time in the male and female genitalia. In special, about the forewings in Bethylinae, we suggest practicable approaches to functional morphology to the venation in the Bethylinae clades. The present study is the most comprehensive cladistic treatment dedicated to the understanding of the evolution of the Bethylinae genera, and the first to consider a global sampling of species of this subfamily. We conclude that the morphological characters unexplored, mainly, of male and female genitalia might offer additional data relevant to more robustly estimate the phylogenetic history of this group. Here, we also promote a first step to direct and encourage future research in Bethylinae using the arrangement of forewing veins, flexion lines and male and female genitalia characters to phylogenetic reconstruction.